Rheumatoid arthritis associated cytokines and therapeutics modulate immune checkpoint receptor expression on T cells - Emerson, Dana; Merriman, Eve; Yachi, Pia P. (Frontiers in Immunology, 2025)
IntroductionWe investigated the impact of rheumatoid arthritis (RA) associated cytokines and standard of care (SOC) RA therapeutics on immune checkpoint receptor (IR) expression on T cells to gain insights to disease pathology and therapeutic avenues.MethodsWe assessed IR expression by flow cytometry on T cell receptor activated T cells cultured in the presence of exogenously added single cytokines or RA patient synovial fluid. We also assessed RA synovial fluid stimulated samples in the presence of various single cytokine neutralizing antibodies or SOC therapeutics, including glucocorticoids, TNF, IL-6 receptor and JAK inhibitors. In addition to IR expression, we measured the impact on cytokine secretion profiles.ResultsRA-associated cytokines modulated IR expression, suggesting a role for these cytokines in regulation of disease pathology. By dissecting the influence of various inflammatory drivers within the RA inflammatory milieu, we discovered distinct regulation of IR expression by various cytokines including IL-10, IFNα/β, and TNF. Specifically, increased expression of TIM-3, PD-1, LAG-3 and CD28 in response to RA synovial fluid was driven by key cytokines including IL-6, IL-10, IL-12, IFNs, and TNF. In addition, SOC RA therapeutics such as glucocorticoids and TNF inhibitors modulated IR and cytokine expression in the presence of RA synovial fluid.ConclusionsThis study points to an important and intricate relationship between cytokines and IRs in shaping immune responses in autoimmune pathology. The modulation of IR expression by RA-associated cytokines and SOC therapeutics provides new insights for the use of targeted treatments in managing RA pathology.